BRCA1/2 pathogenic variants in triple-negative versus luminal-like breast cancers: genotype–phenotype correlation in a cohort of 531 patients. (December 2020) - Incorvaia, Lorena; Fanale, Daniele; Bono, Marco; Calò, Valentina; Fiorino, Alessia; Brando, Chiara; Corsini, Lidia Rita; Cutaia, Sofia; Cancelliere, Daniela; Pivetti, Alessia; Filorizzo, Clarissa; La Mantia, Maria; et al.
Background: Several available data suggest the association between specific molecular subtypes and BRCA1/2 mutational status. Previous investigations showed the association between BRCA1/2 pathogenic variants (PVs) in specific genomic regions and phenotypic variations of cancer relative risk, while the role of PV type and location in determining the breast cancer (BC) phenotypic features remains still unclear. The aim of this research was to describe the germline BRCA1/2 PVs in triple-negative breast cancer (TNBC) versus luminal-like BC and their potential leverage on BC phenotype. Patients & methods: We retrospectively collected and analyzed all clinical information of 531 patients with BC genetically tested for germline BRCA1/2 PVs by Next-Generation Sequencing analysis at University Hospital Policlinico "P. Giaccone" of Palermo (Sicily) from January 2016 to February 2020. Results: Our results corroborate the evidence that BRCA1 -related tumors often have a profile which resembles the TNBC subtype, whereas BRCA2 -associated tumors have a profile that resembles luminal-like BC, especially the Luminal B subtype. Interestingly, our findings suggest that the PVs identified in TNBC were not largely overlapping with those in luminal-like tumors. Differences in the frequency of two PVs potentially associated with different molecular tumor subtypes were observed. BRCA1 -633delC was detected with relatively higher prevalence in patients with TNBC, whereas BRCA2 -1466delT was found mainly in Luminal B tumors, but in no TNBC patient. Conclusion: Future studies examining the type and location of BRCA1/2 PVs within different molecular subtypes are required to verify our hypothesis and could provide an interesting insight into the complex topic of genotype–phenotype correlations. Additionally, a more in-depth understanding of the potential correlations between BRCA PVs and clinical and phenotypic features of hereditary BC syndrome patients could be the key to develop better strategies of prevention and surveillance in BRCA -positive carriers without disease.